English as a Basis for Command Languages for Machines and Some Problems of Spatial Reference - Sondheimer, Norman (University of Wisconsin-Madison Department of Computer Sciences, 1974)
Current research on natural language speech-understanding provides encouragement for the development of systems for the vocal control of machines. However, the designer of a natural language based command language still faces difficulties posed by certain areas of semantics that have not been well studied. One such area is that of spatial reference, which is the way people refer to objects and actions in space. This paper looks at some problems raised by terms used to make spatial references. In particular, the semantics of English locative prepositions and presitional adverbs and a few related terms are analyzed. In light of this analysis, suggestions are made pertaining to the form that the spatial references that these terms convey could take in English-based command languages that require unambiguous reference.